2014
DOI: 10.1159/000366515
|View full text |Cite
|
Sign up to set email alerts
|

An Unusually Severe Case of Dermatosis Neglecta: A Diagnostic Challenge

Abstract: Dermatosis neglecta is a condition secondary to lack of cleanliness, characterized by the formation of hyperkeratotic plaques located in a particular region of the body, usually due to a disability, and it is considered a diagnostic challenge because it can mimic other entities. We present the case of an 18-year-old woman with a 2-month history of progressive brown verrucous plaque in her face. Our first impression was seborrheic dermatitis and she was treated with facial cleanser soap and topic hydrocortisone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
0
24
0
2
Order By: Relevance
“…150075/-/DC1), includes conditions such as acanthosis nigricans, confluent and reticular papillomatosis, tinea versicolour and ichthyosis vulgaris. 3 Dermoscopic examination may help narrow the differential diagnosis if a "stone pavement" pattern is observed, as in our patient. Resolution of the lesions after swabbing with 70% ethyl or isopropyl alcohol confirms the diagnosis.…”
mentioning
confidence: 65%
“…150075/-/DC1), includes conditions such as acanthosis nigricans, confluent and reticular papillomatosis, tinea versicolour and ichthyosis vulgaris. 3 Dermoscopic examination may help narrow the differential diagnosis if a "stone pavement" pattern is observed, as in our patient. Resolution of the lesions after swabbing with 70% ethyl or isopropyl alcohol confirms the diagnosis.…”
mentioning
confidence: 65%
“…However, 70% isopropyl alcohol causes effective clearance of lesions in both. Despite these differences, the distinction between DN and TFFD becomes difficult at times and it seems that there exists clinical and histological overlap between the two conditions 3,4,6,7,9,10,13 . Some authors have suggested that the difference between TFFD and DN is arbitrary and TFFD may be a milder form of DN 14 .…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Frequentemente é uma afecção subdiagnosticada 3,6 e eventos estressantes anteriores ao início do quadro podem atuar como fatores desencadeantes.…”
Section: Discussionunclassified
“…9 O estudo anatomopatológico geralmente não é necessário, mas quando realizado mostra hiperqueratose ortoceratótica, papilomatose e acantose leve sem um infiltrado inflamatório evidente. 4 Vigorosa fricção com gaze embebida em álcool ou sabão e água resulta em resolução completa do quadro. 3 Casos mais resistentes com placas verrucosas podem demandar uso de agentes ceratolíticos e emolientes para facilitar sua remoção.…”
Section: Discussionunclassified